Improving Students' Arabic Speaking Skills Through Flashcard-Based Peer Tutoring Method - Masyitoh Mudafi'ah Haqiqoh; Nandang Sarip Hidayat; Agung Setiyawan (Universitas Ahmad Dahlan, 2025)
The inadequate speaking abilities of class XI students in Arabic language learning at MA Khairul Ummah Batu Gajah present a challenge that necessitates an innovative and participatory solution. This study aims to assess the implementation and effectiveness of a peer tutoring method integrated with flashcard media to enhance students' speaking abilities. A quantitative research approach was employed, utilizing a quasi-experimental design. The study population comprised all 140 class XI students, with a sample of 28 students from class XI IPA II as the experimental group and 26 students from class XI IPA III as the control group. Data collection was conducted through tests. The analysis revealed that the t-count of 7.008 exceeded the t-table value of 2.01 at a 5% significance level, and the significance level (2-tailed) was 0.000, which is less than 0.05. Consequently, H₁ is accepted while H₀ is rejected. These results suggest the method fosters a more active, interactive, and collaborative learning environment. Therefore, this study advocates for the implementation of peer tutoring supported by visual media, such as flashcards, as an effective and engaging strategy for Arabic language instruction.